2021
DOI: 10.1108/ijesm-08-2020-0015
|View full text |Cite
|
Sign up to set email alerts
|

Problems of adoption of solar power and subsequent switching behavior: an exploration in India

Abstract: Purpose The challenges and factors of household adoption and the use of alternative energy sources have been a point of discussion among researchers. The purpose of this study is to apply a variant of the unified theory of adoption and use of technology (i.e. UTAUT 2) to explore the effect of various constructs that influence technology adoption on the consumers’ intention to adopt (and use) solar power generators (SPG) at the household level and the subsequent switching behavior. Design/methodology/approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 72 publications
(104 reference statements)
1
9
0
Order By: Relevance
“…Consumers can adopt solar PV if they can see the real advantages of using it over non-renewable resources. Similarly, a study conducted in India found that consumers are more receptive to adopting new technologies if they believe in the innovative benefits of technology [124]. Thus, in the early stages of its implementation, the Pakistani government must emphasize the advantages of solar PV, and consumers' confidence in solar PV will grow over time.…”
Section: Structural Model Testingmentioning
confidence: 99%
“…Consumers can adopt solar PV if they can see the real advantages of using it over non-renewable resources. Similarly, a study conducted in India found that consumers are more receptive to adopting new technologies if they believe in the innovative benefits of technology [124]. Thus, in the early stages of its implementation, the Pakistani government must emphasize the advantages of solar PV, and consumers' confidence in solar PV will grow over time.…”
Section: Structural Model Testingmentioning
confidence: 99%
“…In the Indian context, multiple studies have been carried out on renewable adoption (Charles and Majid, 2020;Luthra et al, 2015;Mani and Dhingra, 2012), but such studies are perspective analyses in nature and have failed to carry out real-time primary based empirical research as carried out by this study. Kumar et al (2023) and Roy and Mohapatra (2022) have conducted empirical studies on India related to RE adoptions. However, the studies were limited to roof-top solar-based adoption and neglected other renewable alternatives like biofuel.…”
Section: Literature Review 21 Theoretical Frameworkmentioning
confidence: 99%
“…Kumar et al. (2023) and Roy and Mohapatra (2022) have conducted empirical studies on India related to RE adoptions. However, the studies were limited to roof-top solar-based adoption and neglected other renewable alternatives like biofuel.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Looking forward, the government has set out an optimistic agenda for all its people to access safe, reliable and renewable electricity and clean fuel for cooking and mobility (Sangroya et al , 2020). In terms of renewable energy implementation in the energy sector, solar energy holds an upper hand, but it lacks a similar foothold in the fuel market (Roy, 2021). Multiple fuel market reforms like deregulation of petrol and diesel prices have been introduced in the past (Dubash et al , 2018) to reduce fossil fuel subsidy and enable alternate fuel to compete with fossil fuels.…”
Section: Decarbonization In India: a Review Of Literaturementioning
confidence: 99%